Flooring systems from locally grown Casuarina wood: Performance evaluation based on simulated in-service testing - Almahallawi, Tariq Mohamed (AUC Knowledge Fountain, 2018)
In Egypt there is a lack of forestry regions and it depends totally on imported wood from several areas as Europe and Australia. Casuarina Glauca Sieber ex Spreng is an evergreen tree with very hard, heavy and a dark-brown structured wood that is grown extensively in Egypt with very little water consumption (often irrigated using waste water), fast growth rate and a relatively low cost. Almost all of the wide range of wood flooring products are imported including hardwood floors, engineered flooring systems and medium density fiber boards. The main objective of this research is to develop a wood flooring system from locally grown wood (Casuarina Glauca) to be used as an alternative to the imported woods used for flooring systems in the Egyptian market by identifying the various types and classifications of wood flooring systems in Egypt and world-wide. The next step is to determine the relevant standard test methods and procedures and manufacture the required equipment and apparatus according to standards. Then perform the determined tests to a representative sample of the most commonly used hardwood floorings in Egypt to be compared with the proposed Casuarina Glauca flooring system. Finally, identify different finishing techniques and products used in the Egyptian market and studying their effects on performance. The Casuarina Glauca and Oak samples showed no significant statistical difference in the concentrated loading test, falling ball indentation and floor surface indentation from small area loads. This indicates that they have similar resistance to heavy loads, small area loads and impact loads. While the performance of Casuarina Glauca was better in the Janka hardness, rolling load, coefficient of friction and abrasion which indicates higher hardness, resistance to rolling loads and abrasion resistance. The types of coatings compared namely, polyurethane and acrylic polyurethane were not found to contribute significantly to tests such as concentrated loading, falling ball indentation, Janka hardness, rolling load, small area loads indentation however, the effect was observed in the surface wetting, coefficient of friction, abrasion resistance test and the resistance to staining. Samples coated with polyurethane, normal and acrylic, had less doming when exposed to moisture, a higher resistance to abrasion, a smaller coefficient of friction and better resistance to stains and cigarette burns with the acrylic polyurethane providing a slightly better performance.